Performance and Economic Evaluation of Gamhar (Gmelina arborea Roxb.) and Aonla (Emblica officinalis Gaertn.) based Agroforestry Models in Uttarakhand and Uttar Pradesh - Singh, Rambir; Srivastava, Anubha; Singh, Charan (Indian Forester, 2024)
Gamhar (Gmelina arborea Roxb.) and Aonla (Emblica officinalis Gaertn.) both are fast growing species and also short rotation suitable trees for fallow lands, which are capable to fulfill the timber, fuel wood, fruits and other demands of farmers in Uttarakhand and Uttar Pradesh states without making adverse effect on under- storey crops and showed a remarkable performance on fallow lands at Dhaluwala majbata (Haridwar) of Uttarakhand and Fatehpur Pelio (Saharanpur) and Kodapur (Prayagraj) of Uttar Pradesh. G. arborea and E. officinalis based agroforestry models were established in Randomized Block Design at 4 mx5 m and 5 mx5 m spacing along with seasonal agriculture rabi crops like Wheat-Barley-Mustard and kharif crops i.e. Groundnut-Til-Millet at above selected sites. On initial observations, soil at Kodapur (Prayagraj) site was alkaline with 8.25 pH in comparison of sites at Dhaluwala majbata (7.11 pH) and Fatehpur Pelio (7.36 pH). Available Phosphorus was in medium ranges at all sites. Available nitrogen and potassium were in low ranges at Dhaluwala majbata in comparison of sites at Fatehpur Pelio and Kodapur. It was also observed that the both species of G. arborea and E. officinalis are performing well on these fallow lands. The growth parameter of G. arborea and E. officinalis showed a regular increase both in height and girth along with agriculture crops at all sites. The expected B: C ratio and net profit in 8 years rotation were found maximum to be (3.29 and `19,15,320/ha) in model-1 (Gamhar-Groundnut-Wheat-Millet-Urd+til at 4x5 m spacing) followed by model-2 (Gamhar-Groundnut-Wheat-Millet-Urd+til at 5x5 m spacing) with (3.13 and `17,54,028/ha), model-7 (Gamhar-Barley-Dencha-Mustard-Cauliflower-Cabbage at 3m on Boundary) with (2.99 and `19,09,525/ha), model-5 (Gamhar+Aonla Mixed –Groundnut –Wheat –Millet -Urd+til at 4x5m spacing) with (2.60 and `13,46,788/ha), model-6 (Gamhar+Aonla Mixed –Groundnut –Wheat –Millet -Urd+til at 5x5 m spacing) with (2.47 and `13,15,317/ha), model-3 (Aonla-Groundnut-Wheat-Millet-Urd+til at 4x5 m spacing) with (1.94 and `7,84,992/ha) and model-4 (Aonla-Groundnut-Wheat-Millet-Urd+til at 5x5 m spacing) with (1.83 and `6,83,352/ha) respectively. As per net returns and B: C ratio, model-1 (Gamhar-Groundnut-Wheat-Millet-Urd+til at 4x5m spacing) was found more economic viable similarly also model-7 (Gamhar-Barley-Dencha-Mustard-Cauliflower-Cabbage at 3 m on boundary) to other models in expected 8 years rotation.